Excitonic states of poly(para-phenylene) - Lavrentiev, M; Barford, W; Bursill, R (Elsevier, 1999)
Using a recently developed phenomenological Hamiltonian of poly(para-phenylene) and the density matrix renormalization group approach, we investigate the transition from bound to unbound states. Energies and exciton correlation functions of the lowest excited states are calculated. The lowest 1B1u- states situated below the charge gap are found to be bound excitons. The 21Ag+ state, being unbound, represents a band threshold; the exciton binding energy is found to be 0.74 eV.